2022
DOI: 10.1155/2022/8297011
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value and Immunological Role of STEAP1 in Pan-Cancer: A Result of Data-Based Analysis

Abstract: Purpose. This study is aimed at systematically analyzing the expression, function, and prognostic value of six transmembrane epithelial antigen of the prostate 1 (STEAP1) in various cancers. Methods. The expressions of STEAP1 between normal and tumor tissues were analyzed using TCGA and GTEx. Clinicopathologic data was collected from GEPIA and TCGA. Prognostic analysis was conducted by Cox proportional hazard regression and Kaplan-Meier survival. DNA methylation, mutation features, and molecular subtypes of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Researchers have found that ICP genes play a crucial role in the regulation of immune cell infiltration and cancer therapy [23]. We further analyzed the relationship between SMG5 expression and ICP genes and found that all tumors had a part of ICP genes associated with SMG5 expression, and 29 out of 47 ICP genes in LGG were associated with SMG5 expression (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Researchers have found that ICP genes play a crucial role in the regulation of immune cell infiltration and cancer therapy [23]. We further analyzed the relationship between SMG5 expression and ICP genes and found that all tumors had a part of ICP genes associated with SMG5 expression, and 29 out of 47 ICP genes in LGG were associated with SMG5 expression (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…SMG5 mRNA expression levels and cell sensitivity data z-scores (GI50) in 60 different cancer cell lines were retrieved by accessing the NCI-60 database using the CellMiner interface (https://discover.nci.nih.gov/cellminer/) [23], and Pearson’s correlation analysis was used to analyze the correlation between SMG5 expression levels and drug scores.…”
Section: Methodsmentioning
confidence: 99%
“…As a promising candidate target, STEAP1 has been a recent focus of a number of studies targeting prostate cancer, such as antibody-drug conjugation therapy [15] , T cell immunotherapy [16] , fusion protein vaccines [17] , and the early detection of metastatic prostate cancer [11] . The expression pattern of STEAP1 varies among tumor types, and the role of STEAP1 in different aspects of malignant tumor phenotypes is controversial [5] , [18] . High STEAP1 expression in Ewing's sarcoma is a marker of tumor invasiveness and could induce an resultful T cell mediated anti-cancer reaction [19] , [20] .…”
Section: Discussionmentioning
confidence: 99%
“…To improve the prognosis of patients with cancer, an increasing number of studies have identified biomarkers that can predict cancer prognosis through bioinformatics analysis, such as Zhao et al who found that aberrant expression of STEAP1 in pancancer predicted survival and CFS and could be a potential therapeutic target [50]. Chen et al suggested that ALKBH7 may serve as a potential prognostic pancancer biomarker and is involved in the immune response [51].…”
Section: Discussionmentioning
confidence: 99%